Strategi Aktualisasi Nilai-Nilai Karakter Integritas dalam Penguatan Pendidikan Akhlak Dosen FTIK Universitas Cendekia Abditama - Muhammad Zakiyuddin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2025)
This study was motivated by the need to strengthen the moral education of lecturers through the instillation of values of integrity in the FTIK environment at Cendekia Abditama University. The purpose of this study was to formulate strategies for actualizing values of integrity in strengthening the moral education of FTIK lecturers at Cendekia Abditama University. The research method used is qualitative, employing three techniques: observation, interviews, and documentation from April 27, 2025, to August 19, 2025. The research results indicate that exemplary behavior in attitude, actions, and speech, the integration of the Islamic village trilogy into every activity, and the cultivation of academic culture are the strategies employed by FTIK lecturers in actualizing the values of integrity. Thus, these strategies have a positive impact on enhancing students' awareness of the importance of noble moral values in both personal and social life. This study demonstrates that strengthening moral education is inseparable from the practical examples demonstrated through the daily actions of a lecturer. Strengthening moral education through the exemplary behavior and integrity of lecturers not only creates a healthy academic environment but also produces outstanding graduates with noble character.